Kearifan Beragama Suku Sasak dalam Wasiat Runungan Masa Pengalaman Baru Karya TGKH. Zainuddin Abdul Majid - Hendra Gunawan; Rusmin Nurjadin (Departement of Mathematics Education, 2024)
The local wisdom possessed by the Sasak tribe is a wealth that must be maintained. The existence of local wisdom in the Sasak tribal community can be a reflection in sustaining the lives of the people within it. As a work, the devotional testament to a new period of experience consistently provides reflections that can be used as guidelines in social, religious and state life. One of the wisdoms that can be reflected in the behavior of the Sasak people contained in the devotional testaments for the new security period is religious wisdom. The aim of this research is to discover the religious wisdom found in the Sasak tribal community which is based on the devotional testaments of the new experience period by TGKH. Zainuddin Abdul Majid. The method used in this research is qualitative literature study. The data in this research is in the form of the text of the Will for the New Experience Period by TGKH. Zainuddin Abdul Majid. The data collection technique used is documentary study. The data analysis technique that researchers use is qualitative analysis. At the conclusion of this research there are several poetry quotes that characterize this, including; the 72nd verse is part 1, the 73rd verse is part 1, the 110 th verse is part 1, the 65th verse is part 1, and the 60th verse is part 1. The whole poem explains the procedures for worship and the relationship between humans and God and his relationship with fellow humans.